Zarys historii administracji samorządowej w Polsce: Outline of the history of local government in Poland - Suchodolski, Bartłomiej (Management and Administration Journal, 2021)
This article gives an overview of the history of local government in Poland from the thirteenth century to the present day. It discusses the most important legal acts which in the past regulated, and still do, the issues of local government, including The March Constitution, “Law of merger”, The April Constitution, July Manifesto which were announced by the Polish Committee of National Liberation, also, connected with the issue of local government decrees of PCNL and laws which were adopted in the years 1944-1998, and the current Constitution of the Polish Republic.